Integrated landscape approaches to managing social and environmental issues in the tropics: learning from the past to guide the future - Reed, J.D.; Vianen, J. van; Deakin, E.L.; Barlow, J.; Sunderland, Terry C.H. (Wiley, 2016)
Poverty, food insecurity, climate change and biodiversity loss continue to persist as the primary environmental and social challenges faced by the global community. As such, there is a growing acknowledgement that conventional sectorial approaches to addressing often inter‐connected social, environmental, economic and political challenges are proving insufficient. An alternative is to focus on integrated solutions at landscape scales or ‘landscape approaches’. The appeal of landscape approaches has resulted in the production of a significant body of literature in recent decades, yet confusion over terminology, application and utility persists. Focusing on the tropics, we systematically reviewed the literature to: (i) disentangle the historical development and theory behind the framework of the landscape approach and how it has progressed into its current iteration, (ii) establish lessons learned from previous land management strategies, (iii) determine the barriers that currently restrict implementation of the landscape approach and (iv) provide recommendations for how the landscape approach can contribute towards the fulfilment of the goals of international policy processes. This review suggests that, despite some barriers to implementation, a landscape approach has considerable potential to meet social and environmental objectives at local scales while aiding national commitments to addressing ongoing global challenges.